Resection and chemotherapy is the optimal treatment approach for patients with clinically node positive intrahepatic cholangiocarcinoma. Issue 1 (January 2020) - Martin, Sean P.; Drake, Justin; Wach, Michael M.; Ruff, Samantha M.; Diggs, Laurence P.; Wan, Jim Y.; Good, Meghan L.; Dominguez, Dana A.; Ayabe, Reed I.; Glazer, Evan S.; Dickson, Paxton V.; Davis, Jeremy L.; et al.
Abstract: Background: Clinically lymph node positive (cLNP) intrahepatic cholangiocarcinoma (ICC) carries a poor prognosis, without clear management guidelines for the practicing clinician. We sought to evaluate current practice patterns for cLNP ICC, including associations with survival. Methods: The National Cancer Database was queried for patients with cLNP ICC, without extrahepatic metastases. Results: We identified 1023 patients with cLNP ICC, 77%% (n = 784) of whom received chemotherapy alone. Resection was undertaken in 23% (n = 239) of patients and was most commonly utilized in combination with chemotherapy (n = 150). Median survival for all patients was 13.6 months. Patients undergoing resection in combination with chemotherapy were associated with an improved survival (22.5 months) as compared to those patients receiving chemotherapy alone (11.9 months) or resection alone (12.4 months) (p < 0.01). Finally, we compared the survival of patients with cLNP ICC with that of patients with pathologically proved lymph node positive (pLNP) ICC, all of whom were treated with resection with chemotherapy, and found no difference in survival (22.5 months–19.3 months, p = 0.99, respectively). Conclusions: While the decision to pursue resection for ICC is multifactorial and patient specific, the presence of clinically positive LNs should not represent a contraindication.